A global initiative for ecological and evolutionary hologenomics - Leonard, A; Earth Hologenome Initiative Consortium; Alberdi, A (Cell Press, 2024)
The Earth Hologenome Initiative (EHI) is a global collaboration to generate and analyse hologenomic data from wild animals and associated microorganisms using standardised methodologies underpinned by open and inclusive research principles. Initially focused on vertebrates, it aims to re-examine ecological and evolutionary questions by studying host-microbiota interactions from a systemic perspective.